Metoprolol‐induced psoriatic nail disease. (22nd June 2012) - Gin, Alexander; Gin, Douglas; Sinclair, Rodney
Abstract We describe the development of psoriatic nail disease due to metoprolol in a 58‐year‐old woman who was being treated for cardiac arrhythmias. The nail condition was unresponsive to topical and systemic treatments but resolved completely with the withdrawal of metoprolol. The reaction recurred with drug rechallenge and resolved when the drug was ceased.